Organophosphate-induced delayed polyneuropathy: A case report - Galarreta Orbegoso, Jorge (2022)
A case of delayed polyneuropatlzy induced by organoplzosplzorates in an adult female patient lOith background of using insecticides in the agruculture lOithout protection since eight years is presented. Tlze diagnosis lOas confirmed by the finding of positive organophohphorated insecticides in blood and urine by means of the tlzin layers cromatography.Delayed neurotoxicity is a complication observed by the contact with some toxics. It consist of a motorsensitive polyneurophaty with axonal predominance, which usually affects to distal zone of nervous fibers and is manifested in paresthesia and distal weakness of the limbs.The first cause of intoxication is the plague combating agents, being organo-phosplzorates and carbamates which has tlze higher incidence in our environment. Intoxications are more produced in rural zones because of and inadequate protection.As a support of the causistics of this little known pathology in our environment, we reported a case in Santa Ana Service from Hospital Nacional Dos de Mayo.